1992
DOI: 10.1002/bbpc.19920960813
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and isotope effects on addition of atomic hydrogen to benzene in aqueous solution

Abstract: Pulsed ESR has been used to measure rate constants for the addition of hydrogen atoms to benzene as a function of temperature in aqueous solution. At 298 K we obtain k,(aq) = (1.1 + 0.1).109 M -' s-I.Thc average Arrhenius activation energy, E, = 19.1(6) kJ. mol-I, is essentially the same in solution as in the gas phase, but the frequency factor, represented by log(A/M-' s-') = 12.34(9), is 54 times higher than in thc gas. This may be cxplained in terms of solvation of reactants and transition state, with most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 18 publications
8
54
0
Order By: Relevance
“…We estimate the effect as half of the difference in solubility between C 6 H 6 and C 6 H 8 (1,4-cyclohexadiene), i.e., DDH solv =À0.5 kJ mol À1 (Roduner and Bartels, 1992). Assuming this value to be temperature independent, and neglecting DDS solv , the correction brings the theoretical curve further down and in nearly quantitative agreement with experiment, as indicated by the full curve in Fig.…”
Section: Article In Pressmentioning
confidence: 51%
See 1 more Smart Citation
“…We estimate the effect as half of the difference in solubility between C 6 H 6 and C 6 H 8 (1,4-cyclohexadiene), i.e., DDH solv =À0.5 kJ mol À1 (Roduner and Bartels, 1992). Assuming this value to be temperature independent, and neglecting DDS solv , the correction brings the theoretical curve further down and in nearly quantitative agreement with experiment, as indicated by the full curve in Fig.…”
Section: Article In Pressmentioning
confidence: 51%
“…3. Solvent effect on the rate constant for the addition of H to benzene in water, k(aq)/k(gas), according to data from Roduner and Bartels (1992). The broken line gives the predicted value using DG solv (H)=DG solv (H 2 ), and the full line gives a value corrected for the different solvation of C 6 H 7 transition state and C 6 H 6 reactant, DDH solv =0.5 kJ mol À1 (see text).…”
Section: Quantum Effectsmentioning
confidence: 99%
“…The experimental procedure for determining .H atom reaction rate constants has been described in great detail in several previous publications (10)(11)(12)(13), and thus only a short description shall be given here. Hydrogen atoms were generated in aqueous solution by pulse radiolysis, using 3 MeV electrons from a Van de Graaff accelerator.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its great specificity, direct EPR detection of the decay of the .H atom following electron pulse radiolysis was the monitoring method of choice (8,9). The pulsed EPR-based free induction decay (FID) attenuation method (10)(11)(12)(13)(14)(15) used in this study has been demonstrated to be particularly advantageous for such rate constant measurements because of the simple pseudo-first-order scavenging kinetics generally obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The solvation of the H-atom is a separate and, in this context, less important subject, since it is expected that its enthalpy will be small in most solvents. Actually, it can be predicted using the hydrogen molecule as a suitable model [30][31][32], yielding ∆ sln H°(H • ,g) = 5 ± 1 kJ mol -1 for organic solvents [33]. We will now focus on the difference between the solvation enthalpies of a radical and its precursor, according to various models, the methods used to test those models, and the quality of the results they produce.…”
Section: Dh°(r-h)mentioning
confidence: 99%